Analisis Usahatani Kapulaga Desa Tundagan Kecamatan Watukumpul Kabupaten Pemalang - Sambodo, Reo (Musamus University, 2022)
Cardamom is one of Indonesia's biopharmaceutical commodities that is increasingly in demand by the export market, as indicated by the increasing demand from other countries. This study aims to analyze the feasibility of cardamom farming. The data processing method in this study was analyzed by farming analysis, namely by using financial analysis of the R/C ratio. The results of cardamom farming with local varieties are Rp. 186,900,000 with an average production per 1 hectare of 890 kg with a high price of Rp 210,000. The income received by cardamom farmers is Rp. 13,720,500 and the profit obtained by cardamom farmers is Rp. 102,945 000. Based on the results of the calculations in the discussion, it can be concluded that cardamom farming is profitable, it means that cardamom farming is feasible to be developed because the results of the R/C calculation are more than 1, namely 2.2 which means the business is feasible. Keywords: Cardamom, Farming